Effects of structural congestion and surrounding obstacles on the overpressure loads in explosions: experiment and CFD simulations - Bae, Myeong Hyeon; Paik, Jeom Kee (Ships and offshore structures, 2018)
An experimental and numerical study was undertaken to identify the characteristics of overpressure loads in offshore platform models subject to hydrocarbon explosions, with a focus on the structural congestion and surrounding obstacles. A large-scale (one-half) test model of a FLNG (liquefied natural gas floating production storage and offloading unit) topside structure was used for the experiment. Computational fluid dynamics (CFD) were used to calculate the overpressure loads in explosions with varying degrees of structural congestion. The overpressure loads tended to be more significant with the increase in structural congestion because the ventilation of exploded gas was retarded due to the obstacles presented by congested structural elements. Also, the overpressure loads with the surrounding structures are much larger than those without them. Details about the test database are documented to provide a useful reference for other researchers to validate numerical and theoretical methods.